Development of a Three-Tier Diagnostic Test Instrument to Identify Students' Misconceptions on Motion Kinematics Material - Pratama, Bagus; Istiyono, Edi (Impulse: Journal of Research and Innovation in Physics Education, 2024)
This research aims to: (1) Know the construction of the three tier diagnostic test instrument to identify misconceptions of high school students (2) Find out the quality of the three tier diagnostic test instrument to identify misconceptions of high school students (3) Know the misconception profile of high school students (4) Find out The level of practicality of the three-tier diagnostic test instrument for identifying misconceptions of high school students. This type of research is instrument development research using a method adapted from the Oriondo and Antonio model which consists of the test instrument design, test trial and measurement stages. This research was conducted at 4 high schools in Bantul Regency with research subjects of 343 class XI students. Content validity was analyzed using Aiken's V formula. The data analysis technique used is the polytomous item response theory approach according to the Partial Credit Model (PCM). The test characteristics tested include item suitability, reliability, item difficulty level, item characteristic curve, information function and standard error measurement (SEM). The results of the research show that: (1) The construction of the physics research instrument developed consists of 15 questions including aspects, sub-aspects and indicators that have valid and reliable test items, (2) Based on the criteria for the lowest and highest limit of the mean INFIT MNSQ, namely 0, 77 and 1.30 test items all fit the PCM model. The difficulty level of the test items is in the range between -0.561 to +0.330, which means the test items are in the good category because the value is between -2.0 and +2.0. The total information function of the test is relatively high for abilities between -1.4 to +1.5, (3) The students' misconception profile obtained the highest misconceptions in the rectilinear motion sub-material with the medium category, and (4) The practicality of the three-level diagnostic test instrument based on responses students stated that the instrument developed was included in the practical category.